2005
DOI: 10.1007/s11162-004-6287-6
|View full text |Cite
|
Sign up to set email alerts
|

Progress For Women In Academe, Yet Inequities Persist: Evidence from NSOPF:99

Abstract: In this study, we use data from the 1999 National Study of Postsecondary Faculty (NSOPF:99) to measure the unexplained wage gap between men and women in academe. We pay particular attention to how these unexplained wage gaps have changed over time by comparing the results from the 1999 survey to published results from previous national surveys and test for the sensitivity of these findings to the method used for measuring the unexplained wage gap and the type of institution or field being examined. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(63 citation statements)
references
References 30 publications
(60 reference statements)
4
58
0
1
Order By: Relevance
“…Research has indicated that women receive lower salaries (Carr et al 2015, Toutkoushian & Conley 2005 and fewer resources such as research space (Chisholm et al 1999). Moreover, faculty women do more housework at home than their male counterparts (Scheibinger & Gilmartin 2010) and experience more difficulty in achieving work-life balance (O'Laughlin & Bischoff 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Research has indicated that women receive lower salaries (Carr et al 2015, Toutkoushian & Conley 2005 and fewer resources such as research space (Chisholm et al 1999). Moreover, faculty women do more housework at home than their male counterparts (Scheibinger & Gilmartin 2010) and experience more difficulty in achieving work-life balance (O'Laughlin & Bischoff 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Cloud State University, the University of Cincinnati, and the University of South Florida illustrate that pay discrimination proceedings are still being brought by female professors. These findings are not surprising considering reports showing that female faculty, on average, still earn substantially less than male faculty (Ehrenberg, 2003;Euben, 2001;Toutkoushian and Conley, 2005).…”
Section: Measuring Female Pay Inequitiesmentioning
confidence: 66%
“…Without this framework, it would be nearly impossible for institutional researchers to evaluate the compensation practice of an institution and determine if it is appropriate. This work is important to continue given the findings by Toutkoushian and Conley (2005) and others that significant unexplained wage gaps between male and female faculty still persist in academe.…”
Section: Resultsmentioning
confidence: 93%
“…These studies usually focus on trying to estimate whether faculty are paid differently based on nonwork-related characteristics such as gender and race/ethnicity (Ashraf, 1996;Barbezat, 1989Barbezat, , 1991Barbezat, , 2002Ferber, 1974;Hoffman, 1976;Katz, 1973;Ransom and Megdal, 1993;Toutkoushian and Conley, 2005). It is usually the case that the average salary for male faculty exceeds the average for female faculty, and such mean differences could raise concerns within the institution about possible pay discrimination.…”
Section: Equilibrium Wages and Employment In The Academicmentioning
confidence: 99%